Turkey - Africa Institutional Cooperation: Strategic Impacts, Significance and Challenges - Francis Kwesi Kyirewiah; Getachew Toma Bilate (Mediterranean Journal of Social Sciences, 2022)
The development of economic cooperation, diplomacy, and political relations between Turkey and Africa in the past years is attracting many courtesies. Current trends show an increasing engagement and relations between African nations and Turkey which seems to exhibit consistent growth since Ankara declared 2005 as ‘the year of Africa.’ This study examines the institutional cooperation, strategic impacts, their significance, and challenges to Turkey-Africa relations The argument is given based on the fact that Turkish ideologically distanced itself from the global South during and after the Cold War period. However, the fast-paced collaboration in the 21st century signifies a partial revision in its foreign policy orientations towards Africa. In the background of this revisionist orientation, Turkey considers Africa as a way of not only reframing its relations with its nations but also strengthening cooperation with African political and economic institutions. Despite their historical ties, both Africa and Turkey’s cooperation have not transcended to a comprehensive and strategic level. This study finding indicates that Turkey’s growing involvement in Africa reflects its need to establish new markets for its manufactured goods, and its defense and armaments industry and present itself as a relevant regional and global actor different from traditional western players on the continent. What is more, African leaders also seek to attract Turkish Foreign Direct Investment, diversify economic and political partners to reduce dependency, and fuel their state-building projects. Currently, the political cooperation between Turkey and Africa seems to be in good health. Turkey’s endeavors in the field of development cooperation demonstrate its dedication to the efforts aimed at poverty eradication and development for a better future for all. However, both Turkey-Africa’s institutional cooperation is less effective due to a lack of commitments from both sides, inadequate technological resources, political dynamics, and instabilities in some parts of Africa. Received: 26 April 2022 / Accepted: 30 June 2022 / Published: 5 July 2022